Determinants of Firm Value in IDX ESG Leaders: ESG Risk Rating, Financial Performance, and Eco-Efficiency - Niken Rahmawati; Ira Wikartika (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Firm value is an important indicator of corporate performance and investor perception, particularly among companies that apply sustainability principles. The increasing attention to environmental, social, and governance (ESG) practices and environmental efficiency highlights the need for empirical evidence on whether ESG risk rating, financial performance, and eco-efficiency contribute to firm value. This study aims to examine the effects of ESG risk rating, financial performance, and eco-efficiency on firm value among IDX ESG Leaders companies listed on the Indonesia Stock Exchange during 2022–2024. A quantitative methodology was employed, involving a sample of 22 listed companies selected through purposive sampling from a population of 40 companies. Data were collected through documentation from official reports issued by the Indonesia Stock Exchange and the companies’ official websites, and were analyzed using multiple linear regression with SPSS version 27. The findings show that ESG risk rating does not significantly influence firm value, whereas financial performance and eco-efficiency have significant effects on firm value. These results indicate that firm value among IDX ESG Leaders companies is more closely associated with financial performance and eco-efficiency than with ESG risk rating. The findings suggest that investors respond more strongly to financial performance and environmental efficiency when assessing firm value. This study contributes to sustainability accounting and corporate finance literature by providing empirical evidence on the determinants of firm value in ESG-oriented Indonesian listed companies. The practical implication is that companies should maintain strong financial performance and strengthen eco-efficiency practices to enhance firm value, while future studies are encouraged to extend the period of analysis and include other relevant variables.